2006
DOI: 10.1115/1.2709656
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Interfacial Phonon Transport in Si–Ge Heterostructures Using an Atomistic Green’s Function Method

Abstract: An atomistic Green’s function method is developed to simulate phonon transport across a strained germanium (or silicon) thin film between two semi-infinite silicon (or germa-nium) contacts. A plane-wave formulation is employed to handle the translational sym-metry in directions parallel to the interfaces. The phonon transmission function and thermal conductance across the thin film are evaluated for various atomic configurations. The contributions from lattice straining and material heterogeneity are evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
177
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(182 citation statements)
references
References 37 publications
5
177
0
Order By: Relevance
“…We follow the same atomistic Green's function method [23,27] we applied for a single Si/Ge interface [25]. The only difference is that, in this study, we use Si/Ge superlattices as the center region, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We follow the same atomistic Green's function method [23,27] we applied for a single Si/Ge interface [25]. The only difference is that, in this study, we use Si/Ge superlattices as the center region, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Green's function study on Si/Ge superlattices, however, is scarce. Zhang et al [23] briefly discussed the effect of number of interfaces on the overall thermal resistance across multiple Si/Ge interfaces, while transmission function was not detailed. In this study, we use the Green's function method to investigate coherent phonon transport across Si/Ge superlattices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Si (or Ge) is strained to have the same lattice constant as Ge (or Si) along the interface plane to study phonon transmission across Si/Ge interface while the inter-atomic distance in the direction perpendicular to the interface is adjusted according to the Poisson's ratio in Ref. 27. A similar numerical technique has been applied to study the phonon transmission across a TiC/graphene nanoribbon (GNR) interface in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the frequency-dependent phonon transmission across a variety of material interfaces has been studied using the AGF approach, such as the interface in low dimensional atomic chains, 26 strained Si/Ge interface, 27 metal/graphene nanoribbon (GNR) interface, 28 rough interface between two face-centered cubic (FCC) crystals, 29 and more recently across confined material interfaces. 30 However, all the past AGF-based studies on phonon transmission across interfaces [27][28][29][30][31][32] focused on lattice-matched material interfaces, where the inter-atomic distance of one material is usually adjusted to match that in the other material in the directions parallel to the interface to simplify the calculations. For example, Si (or Ge) is strained to have the same lattice constant as Ge (or Si) along the interface plane to study phonon transmission across Si/Ge interface while the inter-atomic distance in the direction perpendicular to the interface is adjusted according to the Poisson's ratio in Ref.…”
Section: Introductionmentioning
confidence: 99%